Detection, by three techniques, of hepatitis B surface antigen (HBsAg) and determination of HBsAg and anti-HBs titres in patients with chronic liver disease. Issue 1 (January 1977) - Chiaramonte, M; Heathcote, J; Crees, M; Sherlock, S
Abstract : The sensitivities of three technqiues used to detect serum hepatitis B surface antigen (HBsAg) were compared in 411 patients with various types of chronic liver disease. Counterimmunoelectrophoresis proved an unreliable test. Two haemagglutination technqiues were slightly less sensitive than radioimmunoassay but were more rapidly performed. Less sensitive techniques were particularly unreliable in active liver disease where HBsAg titres were low. HBsAg was detected in patients with chronic persistent hepatitis, alcoholic liver disease, chronic active liver disease with or without cirrhosis, and primary liver cell carcinoma. Forty-six of the 68 (68%) HBsAg positive subjects were males coming from outside the United Kingdom. The HBsAg titres in 13 subjects with chronic persistent hepatitis were significantly higher (P less than 0-001) than those in 43 subjects with chronic active liver disease. Corticosteroid therapy did not alter the HBsAg titre significantly. None of the 28 HBsAg positive subjects studied serially for up to two years cleared HBsAg from the serum. Anti-HBs was examined by passive haemagglutination and found in 35 subjects, 26 of whom had no evidence of liver disease, 80% came from abroad. Anti-HBs was believed to be of epidemiological rather than of pathological importance.